Numerical solution of non-linear Fredholm-Hammerstein integral equation via Schauder bases. (1st January 2013) - Berenguer, M.I.; Gámez, D.
In this paper, we obtain an approximation of the solution of the nonlinear Fredholm-Hammerstein integral equation by means of a new method for its numerical resolution. The main tools used to establish it are the properties of a Schauder basis in a Banach space and the Banach fixed point theorem.